PENGARUH PERBEDAAN SUHU DAN LAMA PENGASAPAN TERHADAP KADAR AIR, LEMAK DAN GARAM IKAN NILA (Oreochromis niloticus) ASAP - Litaay, Dr. Christina; Jaya, Indra; Trilaksani, Wini; Setiawan, Williandi; Deswati, Ratih (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2022)
Smoking fish is a method of processing to extend the shelf life of the product. To overcome the decline in the quality of tilapia is through a cold smoking process. Cold smoking has a longer shelf life than fish smoked with hot smoking. This study aims to determine the effect of temperature and smoking time on the quality of smoked tilapia using the cold smoking method. The interaction of temperature treatment and smoking time in the smoking process affects the characteristics of the water, fat, and salt content of smoked tilapia. Smoked tilapia produced by a combination of temperature treatment and smoking time has a moisture content of 12.73-20.46%; fat with an average of 16.48-27.17%; and salt by 3.30-4.68%. Temperature treatment of 50-55oC for 48 hours gave a lower moisture content value of 12.73%. The results of this study indicate that differences in temperature and smoking duration affect the moisture, fat, and salt content of smoked tilapia.